Digital services in Poland and the Far East - comparative analysis - Klej, Dominik (Journal of Computer Sciences Institute, 2020)
The following article focuses on ilustrating the content of the master thesis with the same title. The methodology of developed by author digital indicator will be presented, as well as the results and conclusions based on the comparative analysis. The research concerns the comparative analysis between digital services in Poland, Japan and China, based on the IDI, WDC and ITC digital indicators. The analysis is based on publicly available data of digitization.